2018
DOI: 10.1038/s41467-018-07321-8
|View full text |Cite
|
Sign up to set email alerts
|

Translation of non-standard codon nucleotides reveals minimal requirements for codon-anticodon interactions

Abstract: The precise interplay between the mRNA codon and the tRNA anticodon is crucial for ensuring efficient and accurate translation by the ribosome. The insertion of RNA nucleobase derivatives in the mRNA allowed us to modulate the stability of the codon-anticodon interaction in the decoding site of bacterial and eukaryotic ribosomes, allowing an in-depth analysis of codon recognition. We found the hydrogen bond between the N1 of purines and the N3 of pyrimidines to be sufficient for decoding of the first two codon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 74 publications
(91 reference statements)
1
46
0
Order By: Relevance
“…Given that an A:G mismatch at another bystander off-target site, T105T, significantly reduced the editing rate in vivo , subsequent guides should include a mismatch at this site as well. Even though neither bystander off-target editing changed the amino acid, mismatches at these sites will have the benefit of preventing promiscuous inosine decoding ( Hoernes et al, 2018 ; Licht et al, 2019 ), in the case that decoding also occurs at a reasonable frequency in non-dividing neurons, as reported for dividing cells. Regarding off-target editing within the whole transcriptome, as described previously ( Cox et al, 2017 ; Katrekar et al, 2019 ; Vallecillo-Viejo et al, 2018 ), the hyperactive editase resulted in global off-target editing within neurons in the brain.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Given that an A:G mismatch at another bystander off-target site, T105T, significantly reduced the editing rate in vivo , subsequent guides should include a mismatch at this site as well. Even though neither bystander off-target editing changed the amino acid, mismatches at these sites will have the benefit of preventing promiscuous inosine decoding ( Hoernes et al, 2018 ; Licht et al, 2019 ), in the case that decoding also occurs at a reasonable frequency in non-dividing neurons, as reported for dividing cells. Regarding off-target editing within the whole transcriptome, as described previously ( Cox et al, 2017 ; Katrekar et al, 2019 ; Vallecillo-Viejo et al, 2018 ), the hyperactive editase resulted in global off-target editing within neurons in the brain.…”
Section: Discussionmentioning
confidence: 93%
“…Adenosine deaminase enzymes catalyze the hydrolytic deamination of adenosine to inosine in RNA (A-to-I RNA editing) ( Bass and Weintraub, 1987 , 1988 ; Kim et al, 1994 ; Melcher et al, 1996 ; O’Connell et al, 1998 ). Inosine is generally treated as guanosine by the translational machinery ( Basilio et al, 1962 ; Hoernes et al, 2018 ; Licht et al, 2019 ), resulting in codon changes with important consequences for protein function, particularly in the nervous system ( Bhalla et al, 2004 ; Burns et al, 1997 ; Sommer et al, 1991 ). Two catalytically active adenosine deaminase acting on RNA enzymes, ADAR1 and ADAR2, are expressed at high levels in the CNS ( Tan et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…These weak interactions have critical importance for biological macromolecules since they can easy construct and break. Besides, they require less energy which makes them favorable for biological systems …”
Section: Resultsmentioning
confidence: 99%
“…No A-minor interaction interrogates the base pair formed at the third position of the codon/anticodon minihelix, and this position, the wobble position, has long been known to accommodate a variety of non-canonical pairings. Recently, via transfection of HEK cells, it has been demonstrated that nucleobases that do not interact via hydrogen-bonding can participate in decoding when at the wobble position 35 . Nonetheless, it is currently unclear why decoding by the NaM self-pair is favored over decoding by the heteropair.…”
Section: Discussionmentioning
confidence: 99%